Uncovering the inflammatory profile of obese children: examining the link between body mass index for age and insulin resistance in the Gaza Strip - Abu Ghazza, Balsam Said; El Bilbeisi, Abdel Hamid; El Afifi, Amany (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to examine the role of inflammation in the relationship between body mass index (BMI)-for-age and insulin resistance among first-grade students in the Gaza Strip.Materials and methodsA cross-sectional study conducted between March and April 2023 involved 185 students, aged six, from five primary schools. Data were collected via structured questionnaires covering demographics, socio-economic status, lifestyle, and medical history. Anthropometric measurements, including BMI-for-age percentile, waist and hip circumferences, and blood pressure, were recorded. Biochemical analyses measured inflammatory markers (Hs-CRP, IL-6, adiponectin), fasting insulin, fasting plasma glucose, HDL-c, triglycerides, hemoglobin, and HOMA-IR. Statistical analysis was performed using SPSS version 25.ResultsThe study found that 74.6% of students had normal BMI-for-age, while 14.1% were overweight, 8.1% obese, and 3.2% underweight. BMI categories were significantly associated with socio-economic factors, especially place of residence and paternal education. Paternal employment was linked to insulin resistance. A significant association was found between BMI-for-age and insulin resistance, with higher insulin resistance in overweight and obese children. Waist and hip circumferences were significantly linked to BMI and insulin resistance. Hs-CRP and fasting insulin were significantly associated with insulin resistance (P values > 0.05 for all).ConclusionThe study confirms that childhood obesity is closely associated with both inflammation and insulin resistance. Elevated levels of IL-6, Hs-CRP, and insulin in obese children highlight the metabolic risks of childhood obesity. Socio-economic factors, including paternal education and place of residence, significantly influence BMI-for-age, suggesting the need for socio-economic considerations in obesity prevention efforts.